Some aspects of the international mechanism for identifying, searching, seizing and confiscating criminally legalized assets - Kramar, Ruslana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article analyzes the international mechanism in terms of ensuring the procedures for detection, search, seizure of criminal assets, as well as the management of confiscated property of the tested in foreign countries. It has been established that the international anti-money laundering mechanism consists of a number of elements related to asset tracking, such as due diligence by financial institutions and non-financial commercial entities.Based on a study of foreign legislation and law enforcement practices on the freezing, seizure and confiscation of criminal assets, as well as the management of confiscated assets for AML/CFT, some aspects of the legal regulation of confiscation of criminal assets are analyzed and special bodies set up to identify criminal assets confiscation.